Y(1+8y)=4-3x

Simple and best practice solution for Y(1+8y)=4-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y(1+8y)=4-3x equation:


Simplifying
Y(1 + 8y) = 4 + -3x
(1 * Y + 8y * Y) = 4 + -3x
(1Y + 8yY) = 4 + -3x

Solving
1Y + 8yY = 4 + -3x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Reorder the terms:
-4 + 1Y + 3x + 8yY = 4 + -3x + -4 + 3x

Reorder the terms:
-4 + 1Y + 3x + 8yY = 4 + -4 + -3x + 3x

Combine like terms: 4 + -4 = 0
-4 + 1Y + 3x + 8yY = 0 + -3x + 3x
-4 + 1Y + 3x + 8yY = -3x + 3x

Combine like terms: -3x + 3x = 0
-4 + 1Y + 3x + 8yY = 0

The solution to this equation could not be determined.

See similar equations:

| 4ysquared=33 | | 0=-6tx^2+48t+54 | | 32+6b=10 | | v^2-6-12=4 | | h=-6tx^2+48t+54 | | (x-6)*(x+3)=0 | | log^3x+log^3(4)=2 | | 5x/12=3 | | 4.3x+11.9=4.3 | | 2y-5=35 | | 5a-8=0 | | 2x*6x=48 | | 9(11t+2)-26t=99+73t | | x/9=b | | cos^2x*sinx-sinx=0 | | sqrt(-5u+34)=u-4 | | 28000+3000y=3600+2000y | | 3x^2+4x-120=0 | | 8=6(7t-2)-(7+t) | | 3m+4=9 | | 8k^2-5=3 | | 3(6-x+2x)=15 | | -20/10a-90 | | 1-11x=-2 | | 2/5x^2-3/10x=4/5 | | 06k+44=.48k+8 | | 3y-2=4y+3 | | 5(2-3y)=3y+1 | | 4x-32=60+2x | | 5z=13 | | 4/9x7/8 | | 27-18r=-18r+9 |

Equations solver categories